Fantastic beasts : the crimes of Grindelwald : the original screenplay - Rowling, J. K.; Minalima Design (Firm) (New York : Arthur A. Levine Books, 2018)
This screenplay in book form describes the dialogue and action of the film. After Newt Scamander helps to capture Gellert Grindelwald, the criminal soon escapes custody and begins gathering followers under his ideology of keeping magic for pure-blood wizards only. Albus Dumbledore, Grindelwald's truest friend, has no choice but to resist the charismatic leader and ask Newt to help thwart the plans for (wizarding) world domination.
Keywords: Wizards -- Juvenile drama; Animals, Mythical -- Juvenile drama